The Effect of the 2008 Global Financial Crisis on the Capital Structures of Conventional and Islamic Banks in the Gulf Cooperation Council Region - Aldeehani, Talla M. (International Journal of Economics and Financial Issues, 2019)
The paper investigates the determinants of capital structures of conventional banks (CBs) and Islamic banks (IBs) before and after the 2008 global financial crisis. We gathered data on the banking industry of the Gulf Cooperation Countries for the period 2003 - 2016 covering 53 banks, 10 of which are Islamic. Our results indicate that the crisis had significant effects on bank liquidity, lending, profitability, size and growth. They also indicate that the capital structures of CBs and IBs, before and after the crisis are determined differently. Due to the contractual setup and capital adequacy requirements, we believe that IBs, had it not been for the faith, do not enjoy enough maneuverability space to enhance shareholders wealth. Accordingly, questions regarding how much IBs’ clients know about faith and the contradicting provisions of Islamic law in the context of investment decision making were raised. Practical and theoretical implications and recommendations are discussed. Keywords: Capital structure, Islamic banks, financial crisis JEL Classifications: G01, G21, G32 DOI: https://doi.org/10.32479/ijefi.7459